Dosimetric impact from cardiac motion to heart substructures in thoracic cancer patients treated with a magnetic resonance guided radiotherapy system. (January 2021) - Yan, Ran; Chu, Fang-I; Gao, Yu; Yu, Victoria; Yoon, Stephanie; Elashoff, David; Lee, Percy; Hu, Peng; Yang, Yingli
Abstract: Few studies have examined the cardiac volume and radiation dose differences among cardiac phases during radiation therapy (RT). Such information is crucial to dose reconstruction and understanding of RT related cardiac toxicity. In a cohort of nine patients, we studied the changes in the volume and doses of several cardiac substructures between the end-diastolic and end-systolic phases based on the clinical magnetic resonance-guided RT (MRgRT) treatment plans. Significant differences in the volume and dose between the two phases were observed. Onboard cardiac cine MRI holds promise for patient-specific cardiac sparing treatment designs.